Pengembangan E-modul dengan Aplikasi Flip PDF Professional Materi Bilangan Bulat pada Siswa Kelas 6 Sekolah Dasar - Gones Belia; Sri Utaminingsih; Gunawan Setiadi; Eko Darmanto (Journal Prakarsa Paedagogia, 2022)
This study aims to test the feasibility and effectiveness of the e-module with the professional flip pdf application for integer material in 6th grade elementary school students. This research is a type of research and development with nonrandomized experimental methods subject pre-test post-test control group design. The results of the feasibility test based on material expert validation obtained a score of 76, the percentage was 84.44%, the category was very good. Assessment of media experts, obtained a score of 110, the percentage of 81.48%, very good category. The effectiveness test of the independent t-test results obtained a significance score of 0.00 < 0.05. The t-count score shows a value greater than the t-table, which is 5.163>2.0166. The N-gain test obtained a score of 57.28 in the quite effective category. From the research data, it can be concluded that the developed e-module is declared feasible and effective for use in learning.